ANALYSIS OF FISCAL POTENTIAL ON ECONOMIC GROWTH IN CENTRAL JAVA DURING 2020–2023: A PANEL DATA APPROACH - Etma Puji Setowati; Esther Sri Astuti Soeryaningrum Agustin (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the effect of fiscal potential, government spending, and human development on regional economic growth in Central Java during the 2020–2023 period. Gross Regional Domestic Product (GRDP), in logarithmic form, is used as the dependent variable, while the independent variables include local fiscal potential (PAD), government spending, and the Human Development Index (HDI). Using panel data regression with a fixed-effect model on 35 districts/cities, the results reveal that HDI has a significant positive impact on GRDP. Meanwhile, fiscal potential and government spending are found to be statistically insignificant. These findings suggest that enhancing human development is a key factor for boosting economic growth in the region.